Genus Fungi pada Tanah Hutan Mangrove Tercemar Logam Berat di Muara Angke DKI Jakarta - ., Achmad; Nurhayati, Pertiwi Wahyu (Institut Pertanian Bogor (IPB University), 2004)
Mangrove soils in Muara Angke Jakarta were suspected to be polluted with heavy metals. This study describes the analysis to the heavy metal content in those polluted soils. The fungus on those soils was isolated and identified. Results show that heavy metal content of soils of Muara Angke was high, i.e., 1.53 ppm for Pb, 4.59 ppm for Cu and 22.55 ppb for Hg. The fungi that were isolated included Penicilium sp., Eupenicillium sp., Talaromyces sp., Aspergillus sp., Trichoderma sp., and sterile fungi, i.e., fungi that did not produce conidia on PDA medium.